2018
DOI: 10.3390/ijms19051309
|View full text |Cite
|
Sign up to set email alerts
|

Corosolic Acid Induces Non-Apoptotic Cell Death through Generation of Lipid Reactive Oxygen Species Production in Human Renal Carcinoma Caki Cells

Abstract: Corosolic acid is one of the pentacyclic triterpenoids isolated from Lagerstroemia speciose and has been reported to exhibit anti-cancer and anti-proliferative activities in various cancer cells. In the present study, we investigated the molecular mechanisms of corosolic acid in cancer cell death. Corosolic acid induces a decrease of cell viability and an increase of cell cytotoxicity in human renal carcinoma Caki cells. Corosolic acid-induced cell death is not inhibited by apoptosis inhibitor (z-VAD-fmk, a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…Many studies have demonstrated that PA has antitumor and anti-proliferative effects in many cancer cells, such as colon, leukemia, and osteosarcoma cells [ 4 , 21 , 26 ]. PA is known to exert its antitumor effects via STAT3 inactivation, HER2 downregulation, and an increase in intracellular reactive oxygen species (ROS) levels [ 27 ]. In these studies, the effects of PA on cell death and growth inhibition were examined using attached cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that PA has antitumor and anti-proliferative effects in many cancer cells, such as colon, leukemia, and osteosarcoma cells [ 4 , 21 , 26 ]. PA is known to exert its antitumor effects via STAT3 inactivation, HER2 downregulation, and an increase in intracellular reactive oxygen species (ROS) levels [ 27 ]. In these studies, the effects of PA on cell death and growth inhibition were examined using attached cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the PCa, PC-3 and DU145 cell lines, (ER) stress was activated by 0, 5, 10 and 15 µM corosolic acid after 24 and 48 h, through two proapoptotic signaling pathways: The inositol-requiring ER-to-nucleus signal kinase 1/apoptosis signal regulating kinase 1/Jun N-terminal kinase (JNK) pathway and the protein kinase RNA-like ER kinase/eukaryotic initiation factor 2 α/activating transcription factor 4/C/EBP-homologous protein signaling pathway, which induced apoptosis and suppressed cell proliferation (89). However, Woo et al (90) found that the corosolic acid-induced death of human renal carcinoma Caki cells (at 10 µM for 24 h) was inhibited by the use of α-tocopherol (a hydrophobic anti-oxidant that prevents free radical damage), but was not inhibited by benzyloxycarbonyl-Val-Ala-Asp-fluoromethyl ketone (an apoptosis inhibitor), necrostatin-1 (a necroptosis inhibitor), ferrostatin-1 or deferoxamine (ferroptosis inhibitors) (90). Futhermore, corosolic acid induces lipid oxidation, and α-tocopherol markedly prevents corosolic acid-induced lipid peroxidation and cell death.…”
Section: Corosolic Acid Exerts Anticancer Effects In Vitromentioning
confidence: 98%
“…As listed in Table 1, apoptosis of cancer cells is induced through different molecular mechanisms involving mitochondrial mediation and/or caspase activation [54,56,[58][59][60][61][62]; enhancement of sgnal transducer and activator of transcription 3 (STAT3) and/or nuclear factor-κB [63][64][65]; downregulation of HER2 signaling [66]; activation of AMPK or 5-FU through the inhibition of mammalian target of rapamycin [67,68]; impairment of tumor development by inhibiting the immunosuppressive activity of MDSC [69]; promotion of β-catenin degradation [70]; induction of G2/M cell cycle arrest and downregulation of phosphatidylinositol-3-kinase (PI3K)/Akt signaling [71]; disruption of maternal embryonic leucine zipper kinaseforkhead box M1 signaling [72]; activation of nuclear factor erythroid 2related factor 2 [73]; and targeting the vascular endothelial growth factor receptor 2/steroid receptor coactivator/focal adhesion kinase pathway [74]. Inhibition of Caki renal carcinoma by CA is the only exception as cell death is non-apoptotic caused by the generation of lipid peroxidation and reactive oxygen species [75]. In addition, CA induced non-apoptotic cell death in other renal cancer cells (ACHN and A498), breast cancer cells (MDA-MB231), and hepatocellular carcinoma cells (SK-Hep1 and Huh7).…”
Section: Anticancer Propertiesmentioning
confidence: 99%
“…Wong downloaded relevant articles from Science Direct, PubMed, and Google Scholar databases and drafted notes for the manuscript. Enhances the antitumor effects on ovarian carcinoma cells by inhibiting STAT3 and NF-κB [64] BCG823 gastric Induces apoptosis of gastric cancer cells through downregulation of the NF-κB pathway [65] NCI-N87 gastric Downregulates signaling of HER2 which induces cell cycle arrest and apoptosis of gastric cancer cells [66] SNU-601 gastric cancer Activates AMP-activated protein kinase (AMPK) and inhibits mTOR resulting in the growth inhibition and apoptosis of gastric cancer cells [67] SNU-620 gastric carcinoma Enhances the anticancer activities of 5-FU through the inhibition of mTOR in gastric carcinoma cells [68] Murine sarcoma Impairs tumor growth by inhibiting the immunosuppressive activity of MDSC in tumor-bearing mice [69] APC-mutated colon cancer Suppresses proliferation of mutated colon cancer cells through the promotion of β-catenin degradation [70] CaSki cervical cancer Induces apoptosis, G2/M cell cycle arrest, and downregulation of PI3K/Akt signaling in cervical cancer cells [71] Y-79 retinoblastoma Induces cycle arrest and cell apoptosis in retinoblastoma cells through the disruption of MELK-FoxM1 signaling [72] TRAMP-C1 prostate cancer Inhibits the growth of prostate cancer cells by activating Nrf2 [73] Huh7, HepG2, and Hep3B liver carcinoma Inhibits migration of liver carcinoma cells by targeting the VEGFR2/Src/FAK pathway [74] Caki renal carcinoma Induces non-apoptotic cell death through generation of lipid ROS in renal carcinoma cells [75] *…”
Section: Authors' Contributionsmentioning
confidence: 99%